Potential Development of N-Doped Carbon Dots and Metal-Oxide Carbon Dot Composites for Chemical and Biosensing - Sahu, Yogita (2022)
The authors are would like to thank the Department of Chemistry, Government VYT PG Autonomous College Durg, Chhattisgarh, sponsored by DST-FIST (New Delhi), India and the Fundação para a Ciência e a Tecnologia (FCT), Portugal, for the Scientific Employment Stimulus-Institutional Call (CEEC-INST/00102/2018) and the Associate Laboratory for Green Chemistry-LAQV, financed by national funds from FCT/MCTES (UIDP/5006/2020). Publisher Copyright: © 2022 by the authors.